Cardiorenal syndrome: Pathophysiology as a key to the therapeutic approach in an under‐diagnosed disease. Issue 8 (11th October 2022) - Prastaro, Maria; Nardi, Ermanno; Paolillo, Stefania; Santoro, Ciro; Parlati, Antonio L. M.; Gargiulo, Paola; Basile, Christian; Buonocore, Davide; Esposito, Giovanni; Filardi, Pasquale Perrone
Abstract: Cardiorenal syndrome is a clinical condition that impacts both the heart and the kidneys. One organ's chronic or acute impairment can lead to the other's chronic or acute dysregulation. The cardiorenal syndrome has been grouped into five subcategories that describe the etiology, pathophysiology, duration, and pattern of cardiac and renal dysfunction. This classification reflects the large spectrum of interrelated dysfunctions and underlines the bidirectional nature of heart‐kidney interactions. However, more evidence is needed to apply these early findings in medical practice. Understanding the relationship between these two organs during each organ's impairment has significant clinical implications that are relevant for therapy in both chronic and acute conditions. The epidemiology, definition, classification, pathophysiology, therapy, and outcome of each form of cardiorenal syndrome are all examined in this review. Abstract : Cardiorenal syndrome is a pathophysiological disorder that involves both heart and kidneys, in which acute or chronic dysfunction of one organ may induce acute or chronic dysfunction of the other. In both chronic and acute situations, an appreciation of the interaction between heart and kidney has practical clinical implications. Authors consider useful differentiating for clinical reasons the acute (CRS‐1 and CRS‐3), chronic (CRS‐2 and CRS‐4), and systemic (CRS‐5) settings.